التشتت النوعی لمحرکات البحث ومدى الوعی بها والإفادة منها - د. عزة فاروق الجوهرى (المجلة الدولية لعلوم المكتبات والمعلومات)
From the public perspective to organize the digital informationenvironment, we find that the search engines are the biggest tools that regulatethe online environment and allows sources to beneficiaries, The volume ofinformation available on the Internet already amazing. Thus, learn how to usespecialized search tools that are designed to help get information is the vehiclethat enables us to effectively deal with this huge source of information, and thespecifications that characterize one of the search tools is that distinguish themfrom others and determine their effectiveness and efficiency of use. With thedevelopment and services online environment tools have evolved, including thesearch engines and evolved types and multi-v characteristics and patterns of use,perhaps unconsciously on the part of the year the beneficiary; hence embodiedstudy the problem of exposure to the search engines, in particular, representedby this problem in the following question: What kinds of search engines ? Andclassified depending on the mechanism by which it operates and the contentprovided by the researcher? Is there awareness by the researchers and sciencestudents in particular? To achieve this, the study used the methodology ofdescriptive analysis, as the use of device which the questionnaire that has beenpresented to 200 Single of the researchers working Beni Suef Universitycommunity (faculty members and their assistants) questionnaire included a list of40 the types of search engine name to find out the extent of awareness,knowledge and use of these engines, and the results yielded was limited to tentypes of qualitative research engines, as has been proved that there are levels ofquality loopback between the search of one type engines according to individual assessments and additional interactive services and potential feedback. Theproportion of 74% of the study sample they do not use search engines other thanGeneral search engines, as opposed to 26% using other engines. Accordingly,the study recommended that he should be in Arabic and university librariesbother them especially by providing a number of all types of search engineswithin their websites. It also recommended the inclusion within the curriculum ofall university programs interested in digital research tools and how to invest todrive awareness of learning and scientific research system